Laser-assisted friction stir welding of magnesium and magnesium/aluminium dissimilar joints - Hennig, Martin (2013)
The present master thesis is dealing with the influence of workpiece temperature in the process loads, generated during the FSW process. The investigation is focused on welding of the magnesium alloy AZ31. To affect the initial temperature of the joining members, two different methods are investigated. by using a laser, the material is heated and soften local direct in front of the welding tool. In contrast, a heating element, located beneath the workpieces, enable the heating of a laser area. The consequences of both methods are regarded and compared in the investigation. In addition, the comparison to the conventional welding process is made. Thereby, main aspects are the rached load levels as well as surface appearance and tensile properties. the successfully reduction of process forces is obtained for both procedures; however, the tensile properties got worse.